Scutellarin: pharmacological effects and therapeutic mechanisms in chronic diseases - Nie, Shanshan; Zhang, Shan; Wu, Ruipeng; Zhao, Yuhang; Wang, Yongxia; Wang, Xinlu; Zhu, Mingjun; Huang, Peng (Frontiers in Pharmacology, 2024)
Scutellarin (SCU), a flavonoid glucuronide derived from Erigeron breviscapus, exhibits broad pharmacological effects with promising therapeutic potential in treating various chronic diseases. It has demonstrated efficacy in modulating multiple biological pathways, including antioxidant, anti-inflammatory, anti-apoptotic, and vasodilatory mechanisms. These protective roles make SCU a valuable compound in treating chronic diseases such as cerebrovascular diseases, cardiovascular diseases, neurodegenerative disorders, and metabolic diseases. Despite its multi-targeted effects, SCU faces challenges such as low bioavailability and limited clinical data, which hinder its widespread therapeutic application. Current research supports its potential to prevent oxidative stress, reduce inflammatory responses, and enhance cell survival in cells and rats. However, more comprehensive studies are required to clarify its molecular mechanisms and to develop strategies that enhance its bioavailability for clinical use. SCU could emerge as a potent therapeutic agent for the treatment of chronic diseases with complex pathophysiological mechanisms. This review examines the current literature on Scutellarin to provide a comprehensive understanding of its pharmacological activity, mechanisms of action, and therapeutic potential in treating chronic diseases.